2019
DOI: 10.1073/pnas.1911734116
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected intracellular biodegradation and recrystallization of gold nanoparticles

Abstract: Gold nanoparticles are used in an expanding spectrum of biomedical applications. However, little is known about their long-term fate in the organism as it is generally admitted that the inertness of gold nanoparticles prevents their biodegradation. In this work, the biotransformations of gold nanoparticles captured by primary fibroblasts were monitored during up to 6 mo. The combination of electron microscopy imaging and transcriptomics study reveals an unexpected 2-step process of biotransformation. First, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
168
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(184 citation statements)
references
References 65 publications
3
168
0
Order By: Relevance
“…Such organisms have the capability to stick on wet interfaces (for example, mussel and spider-web glues) by removing water from the contact surfaces. Gold (Au) nanoparticles were thought to be stable in biologic environments but it has been recently demonstrated that they can undergo intracellular biodegradation and recrystallisation, with a faster degradation of the smallest size particle [15]. Gold nanoparticles maintain stability on solid silk fibroin and promote the dissolution of degummed silk fibres into silk fibroin in a certain CaCl 2 composition [16].…”
Section: Introductionmentioning
confidence: 99%
“…Such organisms have the capability to stick on wet interfaces (for example, mussel and spider-web glues) by removing water from the contact surfaces. Gold (Au) nanoparticles were thought to be stable in biologic environments but it has been recently demonstrated that they can undergo intracellular biodegradation and recrystallisation, with a faster degradation of the smallest size particle [15]. Gold nanoparticles maintain stability on solid silk fibroin and promote the dissolution of degummed silk fibres into silk fibroin in a certain CaCl 2 composition [16].…”
Section: Introductionmentioning
confidence: 99%
“…1 On the other hand, oxidative degradation is an integral part of the life cycle of nanomaterials, especially when used in fuel cells 2,3 and biological media. [4][5][6][7][8] Therefore, understanding the atomicscale mechanisms of nanomaterial dissolution in liquid electrolyte is of primary importance to design more efficient nanotechnologies. In that regards, liquid cell transmission electron microscopy (LCTEM) has become a method of choice to observe the oxidative etching of individual nanostructures such as metallic nanoparticles [9][10][11][12][13][14][15][16][17] and nanoalloys [18][19][20][21] and it has provided a unique observation window on the intermediate nanostructures formed during these dynamic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation-induced plasmon coupling can be efficient enough to generate photoacoustic signals, even for small sizes of AuNP (<30 nm) with the advantages of better penetrating the tumor and facilitating elimination or degradation, as compared to larger NIR-absorbing gold nanorods or nanostars. [33][34][35] Since AuNP endocytosis can lead to highly dense clustering within intracellular compartments, 36,37 it might narrow interparticle gaps (<2 nm) 26 and facilitate the plasmon coupling phenomenon only in situ inside the cells. The plasmon coupling effect and its association with the appearance of a secondary LSPR were well demonstrated by the conformation of discrete AuNP-based structures, i.e., dimers and trimers, 38 or more complex self-assemblies of gold nanoparticles into linear, globular, or fractal clusters.…”
Section: Introductionmentioning
confidence: 99%